Using leading and lagging indicators for forest restoration - Ota, Liz; Firn, Jennifer; Chazdon, Robin L.; Gregorio, Nestor; Mukul, Sharif A.; Viani, Ricardo A. G.; Romero, Claudia; Herbohn, John (The Journal of applied ecology, 2021)
Forest restoration targets are often planned, implemented, measured and reported based on few short‐term lagging indicators (i.e. indicators of realised outcomes), such as the number of seedlings and area planted. We propose the use of leading indicators, which denote likelihood of a certain outcome (e.g. odds that seedlings are of quality and properly planted) to complement lagging indicators and describe how this construct differs from the current practice and how they can be used in conjunction with available frameworks for forest restoration. Leading indicators have great promise to complement lagging indicators because they address the near‐term factors more likely to influence the progress and performance of restoration efforts. For example, secure land tenure (leading indicator) can increase the likelihood of long‐term maintenance and protection (lagging indicator), and the use of best practices in quality seedling production (leading indicator) can increase survival rate (lagging indicator). By observing near‐term leading indicators, management can be adapted towards a goal. Long‐term impacts cannot be verified in the early stages of forest restoration, hence claiming success within the length of project cycles is often unrealistic. Reporting on leading indicators can inform the likelihood that forest restoration goals will be achieved in the longer term. Synthesis and applications. Leading indicators complement lagging indicators and can be used in forest restoration beyond monitoring and evaluation. Indicators can also be used in the design, adaptive management and reporting of restoration interventions. Leading indicators can be used to identify issues that might prevent success in a timely manner so they can be addressed. Resumo Os objetivos da restauração florestal são frequentemente planejados, implementados, medidos e relatados baseados em poucos indicadores defasados (i.e. indicadores de resultados observados) de curto prazo, como o número de mudas e área plantada. Propomos o uso de indicadores antecedentes, os quais denotam a probabilidade de um certo resultado (e.g. chances de que as mudas são de qualidade e propriamente plantadas), para complementar indicadores defasados e descrever como esse construto difere das práticas atuais e como eles podem ser utilizados conjuntamente com abordagens de enquadramento de restauração florestal atuais. Indicadores antecetentes são promissores para complementar indicadores defasados porque eles se referem a fatores de curto prazo que mais provavelmente influenciarão o progresso e a performance de esforços relacionados a restauração. Por exemplo, seguridade de posse de terra (indicador antecedente) pode aumentar as chances de manutenção e proteção a longo prazo (indicador defasado), e o uso de boas práticas em produção de mudas de qualidade (indicador antecedente) podem aumentar a taxa de sobrevivência de mudas (indicador defasado). Observando‐se indicadores antecedentes, o manejo pode ser adaptado em direção aos objetivos. Impactos de longo prazo não podem ser verificados nos estágios iniciais de restauração, portanto alegar sucesso durante o ciclo do projeto é comumente irrealista. O relato de indicadores antecedentes pode informar a probabilidade de que os objetivos da restauração florestal serão alcancados no longo prazo. Síntese e aplicações. Indicadores antecedentes complementam indicadores defasados e podem ser utilizados em restauração florestal alem do monitoramento e avaliação. Indicadores também podem ser usados no planejamento, manejo adaptativo e relatório de intervenções de restauração. Indicadores antecedentes podem ser usados para a identificação de questões que podem impedir o sucesso da restauração em tempo hábil para que eles possam ser abordados. Leading indicators complement lagging indicators and can be used in forest restoration beyond monitoring and evaluation. Indicators can also be used in the design, adaptive management and reporting of restoration interventions. Leading indicators can be used to identify issues that might prevent success in a timely manner so they can be addressed.